2012
DOI: 10.5195/ijt.2012.6100
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Speech-Language Pathologists on the Use of Telepractice in Schools: Quantitative Survey Results

Abstract: This research surveyed 170 school-based speech-language pathologists (SLPs) in one northeastern state, with only 1.8% reporting telepractice use in school-settings. These results were consistent with two ASHA surveys (2002; 2011) that reported limited use of telepractice for school-based speech-language pathology. In the present study, willingness to use telepractice was inversely related to age, perhaps because younger members of the profession are more accustomed to using technology. Overall, respondents wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
2
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(81 citation statements)
references
References 16 publications
4
68
2
3
Order By: Relevance
“…This is consistent with other studies that have found that exposure to telepractice is associated with more positive beliefs regarding its use (175,176,182,183,219). Tucker (175) has suggested that SLPs with greater awareness, experience, and confidence in the use of telepractice will be more willing to implement it with their patients.…”
Section: Speech-language Pathologists' Experiences Of Providing Telepsupporting
confidence: 90%
See 4 more Smart Citations
“…This is consistent with other studies that have found that exposure to telepractice is associated with more positive beliefs regarding its use (175,176,182,183,219). Tucker (175) has suggested that SLPs with greater awareness, experience, and confidence in the use of telepractice will be more willing to implement it with their patients.…”
Section: Speech-language Pathologists' Experiences Of Providing Telepsupporting
confidence: 90%
“…A number of papers have confirmed the efficacy of fluency management via telepractice (211,(221)(222)(223)(224)(225)(226), and previous surveys by ASHA (176) and Tucker (175) found that 46% and 29% of SLPs (respectively) have provided fluency services via telepractice. Most respondents had used custom-built hardware-based equipment, presumably because most large tertiary hospitals have access to this technology.…”
Section: Speech-language Pathologists' Experiences Of Providing Telepmentioning
confidence: 79%
See 3 more Smart Citations